2002
DOI: 10.1104/pp.003442
|View full text |Cite
|
Sign up to set email alerts
|

Heterology Expression of the ArabidopsisC-Repeat/Dehydration Response Element Binding Factor 1 Gene Confers Elevated Tolerance to Chilling and Oxidative Stresses in Transgenic Tomato

Abstract: In an attempt to improve stress tolerance of tomato (Lycopersicon esculentum) plants, an expression vector containing an Arabidopsis C-repeat/dehydration responsive element binding factor 1 (CBF1) cDNA driven by a cauliflower mosaic virus 35S promoter was transferred into tomato plants. Transgenic expression of CBF1 was proved by northern-and western-blot analyses. The degree of chilling tolerance of transgenic T 1 and T 2 plants was found to be significantly greater than that of wild-type tomato plants as mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
292
3
7

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 429 publications
(330 citation statements)
references
References 49 publications
(30 reference statements)
20
292
3
7
Order By: Relevance
“…Recent findings indicate that there is cross talk between two stress-signaling pathways in Arabidopsis (Shinozaki and Yamaguchi-Shinozaki, 2000). Recently, we also observed that transgenic CBF1 tomato plants have enhanced chilling tolerance as compared with wild-type plants (Hsieh et al, 2002). These results in combination with the results in this study confirm that the enhancement of stress tolerance phenomenon in transgenic tomato plants might be conferred by multiple defense systems.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Recent findings indicate that there is cross talk between two stress-signaling pathways in Arabidopsis (Shinozaki and Yamaguchi-Shinozaki, 2000). Recently, we also observed that transgenic CBF1 tomato plants have enhanced chilling tolerance as compared with wild-type plants (Hsieh et al, 2002). These results in combination with the results in this study confirm that the enhancement of stress tolerance phenomenon in transgenic tomato plants might be conferred by multiple defense systems.…”
Section: Discussionsupporting
confidence: 80%
“…Previously, internode length has been reported to have a positive correlation with GA content (Ross et al, 1989). Recently, we found that the internode length of transgenic plants could be recovered by applying GA 3 exogenously (Hsieh et al, 2002). It was of interest to know whether the resistance to water deficit stress of transgenic tomato plants would be affected after GA 3 treatment.…”
Section: Water Deficit Resistance Was Not Affected By Applying Ga 3 Imentioning
confidence: 99%
See 2 more Smart Citations
“…Adaptation processes include an array of biochemical and physiological alterations such as changes in lipid composition from saturated to unsaturated form, increased sugar content and other osmoltytes, as well as protein contents and enzyme activities (Guy 1990;Thomashow 1999). Specific proteins are induced in compliance to low temperature that help cells to cope up with chilling and freezing stress (Thomashow 1999;Knight et al 1999;Tahtiharju and Palva 2001;Gong et al 2002;Hsieh et al 2002). The functions of cold stressinduced proteins include metabolism of carbohydrates, lipids, and phenylpropanoids, as antioxidants, molecular chaperones, mRNA binding proteins, proteinase inhibitors and antifreeze proteins, and also tolerance to cellular dehydration caused by extra-cellular freezing (Mohapatra et al 1989;Guy 1990;Thomashow 1999).…”
Section: Introductionmentioning
confidence: 99%